SMART LETTER BOX FOR HIGH-RISE RESIDENTIAL BUILDING - Azhar, Nurul Syuhada (Journal of Computing Technologies and Creative Content, 2019)
Smart letter box system is a relevant technology for today's use. There are a lot of projects related to smart letter boxes have been created. However, there is still no smart letterboxes created for high-rise residential buildings. Smart letter box for high-rise residential building will enable residents and residential management to manage matters related to postal and letter boxes. Residents will get notification every time new letter arrived at their letter box and they can keep track records of all letters that have arrived. Residential management will also be easy to deal with residents because they can send notification to respective resident and can send general announcement to all residents.